2016
DOI: 10.1080/03602532.2016.1189560
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of oxidative stress in the toxicity and metabolism of quinoxaline 1,4-di-N-oxides in vitro and in vivo

Abstract: Quinoxaline 1,4-dioxide derivatives (QdNOs) have been widely used as growth promoters and antibacterial agents. Carbadox (CBX), olaquindox (OLA), quinocetone (QCT), cyadox (CYA) and mequindox (MEQ) are the classical members of QdNOs. Some members of QdNOs are known to cause a variety of toxic effects. To date, however, almost no review has addressed the toxicity and metabolism of QdNOs in relation to oxidative stress. This review focused on the research progress associated with oxidative stress as a plausible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 142 publications
(280 reference statements)
0
24
0
Order By: Relevance
“…Numerous studies have shown the toxicity of olaquindox in vivo [ 12 , 13 ], but it is more important to evaluate the genotoxicity and cytotoxicity of olaquindox. Previous studies have shown that olaquindox could induce marked cytoxicity and genotoxicity in African green monkey cell lines (Vero cells) and HepG2 cells [ 7 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the toxicity of olaquindox in vivo [ 12 , 13 ], but it is more important to evaluate the genotoxicity and cytotoxicity of olaquindox. Previous studies have shown that olaquindox could induce marked cytoxicity and genotoxicity in African green monkey cell lines (Vero cells) and HepG2 cells [ 7 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The more convenient method for the synthesis of the starting material 2‐amino‐3‐cyano‐6‐methylquinoxaline‐1,4‐dioxide ( 3 ) by the reaction of 5‐methylbenzo[ c ] oxadiazole1‐oxide with malononitrile in the presence of triethylamine as a catalyst and DMF as a solvent was achieved. The scarlet red product was identified as component 3 with 75% yield and melting point 220–222°C .…”
Section: Resultsmentioning
confidence: 99%
“…Quinoxaline‐1,4‐dioxide derivatives are a class of substances possessing a broad spectrum of pharmacological activities, such as anticancer especially in solid tumor treatment , hypoxia‐selective activity , antibacterial , antifungal , and antimycobacterial . Quinoxaline‐1,4‐dioxide derivatives with three fused membered rings show a significant pharmaceutical importance , for example, pyridoquinoxaline, which is used as anticonvulsant and imidazoquinoxaline as receptor antagonists .…”
Section: Introductionmentioning
confidence: 99%
“…Olaquindox is used as a feed additive, but the toxic effects of olaquindox have drawn public attention. A large number of animal studies have revealed that oxidative stress damage in mice tissues, including liver, kidney and adrenal gland, could be caused by treatment with QdNOs such as olaquindox, quinocetone, carbadox and their metabolites [ 7 , 21 , 22 ]. Nevertheless, molecular mechanism research in an in vitro model is particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress damage, caused by excessive reactive oxygen species (ROS), has been suggested as a plausible mechanism for QdNO-induced toxicity and metabolism studies suggest that oxidative stress plays a critical role in QdNOs-induced cytotoxicity [ 7 ]. It has been inferred that the genotoxic effects caused by olaquindox were perhaps due to ROS-induced oxidative DNA damage in human hepatoma G2 (HepG2) cells [ 3 ].…”
Section: Introductionmentioning
confidence: 99%